2004
DOI: 10.1152/physiolgenomics.00056.2004
|View full text |Cite
|
Sign up to set email alerts
|

Fructose-responsive genes in the small intestine of neonatal rats

Abstract: The intestinal brush border fructose transporter GLUT5 (SLC2A5) typically appears in rats after weaning is completed. However, precocious consumption of dietary fructose or in vivo perfusion for 4 h of the small intestine with high fructose (HF) specifically stimulates de novo synthesis of GLUT5 mRNA and protein before weaning is completed. Intermediary signals linking the substrate, fructose, to GLUT5 transcription are not known but should also respond to fructose perfusion. Hence, we used microarray hybridiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 40 publications
6
42
0
Order By: Relevance
“…Furthermore, it is known that glucocorticoid hormones (Si, Slc2a5 and Treh) and thyroid hormones (Si, Slc2a5 and Treh) enhance intestinal gene expressions during the transient suckling-weaning period (4,5,13,32). In addition, the expressions of these genes are known to be upregulated by dietary carbohydrate (9,10,51,52). Therefore, the changes in gene expression between days 13 and 27 detected in our microarray analysis may be regulated by these hormones and dietary factors.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Furthermore, it is known that glucocorticoid hormones (Si, Slc2a5 and Treh) and thyroid hormones (Si, Slc2a5 and Treh) enhance intestinal gene expressions during the transient suckling-weaning period (4,5,13,32). In addition, the expressions of these genes are known to be upregulated by dietary carbohydrate (9,10,51,52). Therefore, the changes in gene expression between days 13 and 27 detected in our microarray analysis may be regulated by these hormones and dietary factors.…”
Section: Discussionmentioning
confidence: 74%
“…Agbemafle et al ( 8 ) examined glucocorticoid hormoneresponsive genes during the suckling period by microarray analysis. Cui et al ( 9,10 ) showed that fructoseresponsive genes, such as glucose-6-phosphatase, fructose-1, 6-bisphosphatase and the PI3 kinase cascade, were upregulated by fructose perfusion in weaning rats. However, these observations only focused on glucocorticoid hormone-or fructose-responsive genes, and the detailed changes in gene expression in the rat small intestine during the transient suckling-weaning period remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…to stimulate phosphofructo-2-kinase/fructose-2,6-bisphosphatase transcription in neonatal rat intestine (9).…”
Section: Discussionmentioning
confidence: 99%
“…In suckling rats younger than 14 days, gavage feeding or perfusion in vivo of fructose has no effect on the already low levels of GLUT5 expression and activity ( Fig. 1) (38,45,74). This is understandable since milk is fructose free and there is no luminal signal that can stimulate GLUT5.…”
Section: Physiology and Functionmentioning
confidence: 95%